Synthesis And Characterization Of Hematite Nanoparticles As Active Photocatalyst For Water Splitting Application - Chin, Sze Mei; Sufian, Suriati; Abd Razak, Jeefferie (Trans Tech Publications, Switzerland, 2014)
This paper highlights on the hydrogen production through photocatalytic activity by using hematite nanoparticles synthesized from self-combustion method based on different stirring period. The morphologies and microstructures of the nanostructures were determined using Field-Emission Scanning Electron Microscope (FESEM), X-Ray Diffractometer (XRD) and Particle Size Analyser(PSA). Besides that, surface area analyser was used to determine the BET surface area of the hematitesamples. The hematite nanocatalyst as-synthesized are proven to be rhombohedral crystalline hematite (α-Fe2O3) with particle diameters ranging from 60-140 nm. The BET specific surface area of hematite samples increased from 5.437 to 7.6425 m2/g with increasing stirring period from 1 to 4 weeks. This caused the amount of hydrogen gas produced from photocatalytic water splitting to increase as well.